Diversity of Iron Oxidizers in Groundwater-Fed Rapid Sand Filters: Evidence of Fe(II)-Dependent Growth by Curvibacter and Undibacterium spp. - Gülay, Arda; Çekiç, Yağmur; Musovic, Sanin; Albrechtsen, Hans-Jørgen; Smets, Barth F. (Frontiers in Microbiology, 2018)
Although earlier circumstantial observations have suggested the presence of iron oxidizing bacteria (IOB) in groundwater-fed rapid sand filters (RSF), ferrous iron (Fe(II)) oxidation in this environment is often considered a chemical process due to the highly oxic and circumneutral pH conditions. Due to the low water temperature (5–10°C), typical of groundwaters, on the other hand, rates of chemical Fe(II) oxidation may be reduced, which may allow IOB to grow and compete with chemical Fe(II) oxidation. Hence, we hypothesized that IOB are active and abundant in groundwater-fed RSFs. Here, we applied a combination of cultivation and molecular techniques to isolate, quantify, and confirm the growth of IOB from groundwater-fed rapid sand filters, operated at different influent Fe(II) concentrations. Isolates related to Undibacterium and Curvibacter were identified as novel lineages of IOB. Gallionella spp. were dominant in all waterworks, whereas Ferriphaselus and Undibacterium were dominant at pre-filters of those receiving groundwaters with high (>2 mg/l) Fe(II) concentrations. The high density and diversity of IOB in groundwater-fed RSFs suggest that neutrophilic iron oxidizers may not be limited to oxic/anoxic interfaces.